Considerations for Setting up a Small-Animal Imaging Facility - Klaunberg, Brenda A. (Lab Anim (NY), 2004)
Imaging techniques allow for the conduct of noninvasive, in vivo longitudinal small-animal studies, but also require access to expensive and complex equipment, and personnel who are properly trained in their use. The authors describe their planning and staffing of the NIH Mouse Imaging Facility, and highlight important issues to consider when designing a similar facility.